Improving Students’ Mastery of Simple Past Tense in Recount Text Writing through Game Based Learning - Rafida Dian Puspita; Windy Citra Negara; Linda Mayasari (PROCEEDING UMSURABAYA, 2026)
This study aims to improve the recount text writing skills of tenth-grade students through the implementation of the Game-Based Learning (GBL) method using the "Treasure Hunt" game. Preliminary study conducted in class X-4 at SMAN 20 Surabaya revealed that many students experienced difficulties in accurately using the simple past tense in recount text writing. Out of 35 students, 62.86% (22 students) scored below the Kriteria Ketuntasan Minimal (KKM). This research employed a Classroom Action Research (CAR) approach, consisting of four stages: planning, implementation, observation, and reflection, conducted over two cycles. In the first cycle, only 51% of students met the KKM. However, in the second cycle, after the application of GBL through the "Treasure Hunt" game, the percentage of students who met the KKM significantly increased to 97%, with an average score of 91. These results indicate that GBL effectively creates an engaging learning environment, enhances students’ motivation and active participation, and significantly improves their ability to write recount texts using the simple past tense. Therefore, the implementation of game-based learning is recommended as an alternative strategy in English language instruction, particularly for enhancing students’ writing competence.